Human OX40 tunes the function of regulatory T cells in tumor and nontumor areas of hepatitis C virus–infected liver tissue. Issue 5 (26th June 2014) - Piconese, Silvia; Timperi, Eleonora; Pacella, Ilenia; Schinzari, Valeria; Tripodo, Claudio; Rossi, Massimo; Guglielmo, Nicola; Mennini, Gianluca; Grazi, Gian Luca; Di Filippo, Simona; Brozzetti, Stefania; Fazzi, Katia; et al.
<x xml:space="preserve">Abstract</x> Regulatory T cells (Tregs) can be considered as a mixed population of distinct subsets, endowed with a diverse extent and quality of adaptation to microenvironmental signals. Here, we uncovered an opposite distribution of Treg expansion, phenotype, and plasticity in different microenvironments in the same organ (liver) derived from patients with chronic hepatitis C: On the one side, cirrhotic and tumor fragments were moderately and highly infiltrated by Tregs, respectively, expressing OX40 and a T‐bethighIFN‐γ– "T‐helper (Th)1‐suppressing" phenotype; on the other side, noncirrhotic liver specimens contained low frequencies of Tregs that expressed low levels of OX40 and highly produced interferon‐gamma (IFN‐γ; T‐bet+IFN‐γ+), thus becoming "Th1‐like" cells. OX40‐expressing and Th1‐suppressing Tregs were enriched in the Helios‐positive subset, carrying highly demethylated Treg cell‐specific demethylated region that configures committed Tregs stably expressing forkhead box protein 3. OX40 ligand, mostly expressed by M2‐like monocytes and macrophages, boosted OX40+ Treg proliferation and antagonized the differentiation of Th1‐like Tregs. However, this signal is counteracted in noncirrhotic liver tissue (showing various levels of inflammation) by high availability of interleukin‐12 and IFN‐γ, ultimately leading to complete, full Th1‐like Treg differentiation. Conclusion: Our data demonstrate that Tregs can finely adapt, or even subvert, their classical inhibitory machinery in distinct microenvironments within the same organ. (Hepatology 2014;60:1494–1507)